2022
DOI: 10.11604/pamj.2022.41.268.26875
|View full text |Cite
|
Sign up to set email alerts
|

Health insurance in private and public health facilities in Southwestern Nigeria: what determines clients´ satisfactionwith quality of service?

Abstract: Introduction: insured-persons have complained about poor quality of services rendered by health care providers, which has consequently affected their satisfaction with care received. The objectives of this study aimed to identify the determinants of satisfaction and compare the level of clients´ satisfaction with quality of care received in both public and private health care facilities, in Oyo-State, Nigeria. Methods: this was a cross sectional study, comparative in design. A total number of 300 cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 18 publications
1
0
0
Order By: Relevance
“…However, individuals' perceptions toward the quality of healthcare services were significantly associated with age, occupation, region, and experiences of insurance schemes in Ghana (Nsiah-boateng et al, 2018). In this study, almost the same result was obtained, For example, dissatisfaction was observed for long waiting times (74%), and other sociodemographic characteristics such as age, educational level, and occupation were significantly associated with satisfaction in Nigeria (Akande et al, 2022). These findings are also similar to our study.…”
Section: Discussionsupporting
confidence: 88%
“…However, individuals' perceptions toward the quality of healthcare services were significantly associated with age, occupation, region, and experiences of insurance schemes in Ghana (Nsiah-boateng et al, 2018). In this study, almost the same result was obtained, For example, dissatisfaction was observed for long waiting times (74%), and other sociodemographic characteristics such as age, educational level, and occupation were significantly associated with satisfaction in Nigeria (Akande et al, 2022). These findings are also similar to our study.…”
Section: Discussionsupporting
confidence: 88%